Muscle protein metabolism in neonatal alloxan-administered rats: effects of continuous and intermittent swimming training - Ribeiro, Carla [UNESP]; Cambri, Lucieli T. [UNESP]; Dalia, Rodrigo A. [UNESP]; Araujo, Michel B. [UNESP]; Ghezzi, Ana C. [UNESP]; Moura, Leandro P. [UNESP]; Araujo, Gustavo G. [UNESP]; Botezelli, Jose D. [UNESP]; Mello, Maria A. R. [UNESP] (Biomed Central Ltd., 2012)
Background: This study aimed to examine the effects of intermittent and continuous swimming training on muscle protein metabolism in neonatal alloxan-administered rats.Methods: Wistar rats were used and divided into six groups: sedentary alloxan (SA), sedentary control (SC), continuous trained alloxan (CA), intermittent trained alloxan (IA), continuous trained control (CC) and intermittent trained control (IC). Alloxan (250 mg/kg body weight) was injected into newborn rats at 6 days of age. The continuous training protocol consisted of 12 weeks of swimming training in individual cylinder tanks while supporting a load that was 5% of body weight; uninterrupted swimming for 1 h/day, five days a week. The intermittent training protocol consisted of 12 weeks of swimming training in individual cylinder tanks while supporting a load that was 15% of body weight; 30 s of activity interrupted by 30 s of rest for a total of 20 min/day, five days a week.Results: At 28 days, the alloxan animals displayed higher glycemia after glucose overload than the control animals. No differences in insulinemia among the groups were detected. At 120 days, no differences in serum albumin and total protein among the groups were observed. Compared to the other groups, DNA concentrations were higher in the alloxan animals that were subjected to continuous training, whereas the DNA/protein ratio was higher in the alloxan animals that were subjected to intermittent training.Conclusion: It was concluded that continuous and intermittent training sessions were effective in altering muscle growth by hyperplasia and hypertrophy, respectively, in alloxan-administered animals.
Keywords: DMT2; exercise training; protein synthesis; hypertrophy muscle